The Burden of Pneumococcal Pneumonia – Experience of the German Competence Network CAPNETZ - Pletz, M. W.; von Baum, H.; van der Linden, M.; Rohde, G.; Schütte, H.; Suttorp, N.; Welte, T. (Pneumologie, 2012)
Background: Pneumococcal pneumonia is still an important cause of mortality. The objective of this study was to compare frequency, clinical presentation, outcome and vaccination status of patients with pneumococcal community-acquired pneumonia (CAP) to CAP due to other or no detected pathogen based on data of the German Network for community-acquired pneumonia (CAPNETZ).Methods: Demographic, clinical and diagnostic data were recorded using standardized web-based data acquisition. Standardized microbiological sampling and work-up were conducted in each patient.Results: 7400 patients with CAP from twelve clinical centers throughout Germany were included. In 2259 patients (32 %) a pathogen was identified, Streptococcus pneumonia being the most frequent (n = 676, 30 % of all patients with identified pathogens). Compared to those with non-pneumococcal pneumonia, patients with pneumococcal pneumonia were more frequently admitted to hospital (80 % vs. 66 %, p < 0.001), had higher CURB score values on admission, had more frequently pleural effusion (19 % vs. 14 %, p = 0.001) and needed more frequently oxygen insufflation (58 % vs. 44 %, p < 0.001). There was no relevant difference in overall mortality.Conclusions: Pneumococcal pneumonia was associated with a more severe clinical course demanding more medical resources as compared to non-pneumococcal pneumonia.